The Role of the Labour Market in Wealth Accumulation (Challenges of the Future, 2021)
Purpose and Originality: Our goal in this paper is to contribute to the professional public by analysing the set of criteria for success, or the failure of the Europe 2020 Strategy in the view of labour market. Our goal is to analyse the effect of labour market in the wealth accumulation because of the Strategy 2020 in two selected countries, namely Slovakia and Croatia.Method: In our paper, we primarily used an econometrics method called simple linear regression, then we used comparative and descriptive methods that helped us to analyse the development of unemployment and employment rate in Slovakia and Croatia and compare them to these labour market indicators for the whole European Union. For the purposes of our analysis and our paper and for the better orientation, we bring in our paper definition of the most important notions mentioned in this paper, so we also used descriptive method. In our paper, therefore, we examine the trace of unemployment in correlation with the wealth rate in two selected countries.Results: Our analysis confirm that the situation on labour market in both analysed countries influences the ability of households to accumulate wealth. Higher employment and lower unemployment rates are associated with greater wealth accumulation. We confirmed by the analysis that the employment rate of Slovakia has increased in the period, in 2018 while the employment rate of Croatia has been a little fluctuating. The employment rate of Croatia raised in 2018. As our results show, the employment rate of Slovakia has increased during the analysed period, while in Croatia this increasing has been smaller. Because of the global financial crisis, the employment rate of both countries decreased, but after these times, the strategies helped to create jobs and raised employment. The situation on the labour market evaluated by the unemployment rate has been almost the same. Although the employment of analysed countries has increased in the observed period, it is still under the employment rate of the European Union.Society: Low unemployment is often associated with a high share of the wealth of the country and households. High unemployment rates and the associated slow economic growth, especially during and after the economic - financial crisis, have forced the European Union to create and modify programs to boost economic growth, increase employment, increase education through innovative approaches etc.Limitations / further research: We consider this topic as important and interesting, and that is why we will continue our research after 2020. We want to do further research, how is the Strategy successful.
Keywords: employment rate; poverty; Strategy Europe 2020; Slovakia; Croatia